Pembelajaran Notasi Musik pada Lagu “Bagimu Negeri” dalam Mata Pelajaran Seni Musik Kelas X SMK YP Gajah Mada Palembang: Penelitian - Al Barrokah; Deria Sepdwiko; Rio Eka Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the learning process of staff notation in the song Bagimu Negeri in the music arts subject of SMK YP Gajah Mada Palembang. Learning staff notation is the main focus in music arts material. This is because understanding and the ability to read STAFF notation will make it easier for students to learn various musical instruments. In order to realize staff notation learning so that reading rhythm and melody and playing it on the instrument becomes better, the right method was chosen by the 10th grade music arts subject teacher, namely implementing an interactive learning method and in accordance with the curriculum that has been set with the needs of students, namely using the drill method or in other words the method of repeated practice from the material that has been arranged. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The results of the study indicate that the learning of staff notation which is arranged systematically and integrated between materials, and applied through the practice method (drill), based on field data shows very satisfying results. This achievement is certainly inseparable from the important role of teachers in mastering and understanding the teaching materials, which are the main keys to the success of the learning process. Furthermore, the conclusions of this study will be presented in the next chapter.